2021
DOI: 10.3390/ijerph18041777
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Two Dry Needling Interventions for Plantar Heel Pain: A Secondary Analysis of an RCT

Abstract: Plantar heel pain is a common cause of foot pain that affects patients’ quality of life and represents a significant cost for the healthcare system. Dry needling and percutaneous needle electrolysis are two minimally invasive treatments that were shown to be effective for the management of plantar heel pain. The aim of our study was to compare these two treatments in terms of health and economic consequences based on the results of a published randomized controlled trial. For this, we evaluated the costs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…To our knowledge, there are no other publications that have analysed the cost-effectiveness of these techniques in patients with PT. However, other studies showed similar results in the comparison of PNE versus DN in the treatment of plantar heel pain, 21 with PNE having an 83% probability of being cost-effective against DN, similar to our study that showed a probability of 93%. In the case of the comparison of DN versus sham needling, we observed that the results were not in favour of DN as suggested by Arias-Buría et al, 42 who found DN to be dominant over control in subacromial pain syndrome.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To our knowledge, there are no other publications that have analysed the cost-effectiveness of these techniques in patients with PT. However, other studies showed similar results in the comparison of PNE versus DN in the treatment of plantar heel pain, 21 with PNE having an 83% probability of being cost-effective against DN, similar to our study that showed a probability of 93%. In the case of the comparison of DN versus sham needling, we observed that the results were not in favour of DN as suggested by Arias-Buría et al, 42 who found DN to be dominant over control in subacromial pain syndrome.…”
Section: Discussionsupporting
confidence: 90%
“…The economic evaluation was conducted from the perspective of a hospital, clinic or health centre. Direct health care costs such as the needling material (sterile gauze, antiseptic solution, US gel, needles), 29,30 the US and PNE device 31 and the staff (physiotherapist) 21 were calculated. The cost of both US and PNE devices was assessed considering the average cost of the equipment (5 or 10 years of amortisation of the equipment cost), the average number of uses per year, and the cost of maintenance, following the guidelines of the Spanish Society of Ultrasound (SEUS) in the case of the US and the approximate cost of the equipment according to market distributor prices.…”
Section: Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it also has some limitations, which impede the generalization of results, as this is a case report and does not have a control. In this study, it was only analyzed the effects of a single session of PN, and therefore it is necessary that future studies analyze the effects of different number of PN sessions and the cost-effectiveness of them, similarly to what has been performed in other studies related to tendinous injuries, 18 myofascial pain 19 and spasticity, 20 , 21 or compared to pharmacological alternatives such as BTX A. 22 Moreover, future studies should be developed with larger samples and with other neurological populations, analyzing also the effect of PN as part of a multimodal treatment, in order to understand which is the additional improvement that PN may achieve in patients with neurological impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, clinicians are using dry needling (DN) to reduce pain [1,2], increase range of motion and flexibility [3], enhance performance [4], reduce spasticity [5], or improve fascial and scar tissue mobility [6,7]. Dry needling is a safe and cost-effective treatment approach [8][9][10][11], but there is no literature informing clinicians whether DN can be applied safely in patients with altered coagulation. Potentially, patients taking antithrombotic drugs may have an increased risk of suffering bleeding complications when being treated with DN.…”
Section: Introductionmentioning
confidence: 99%